Zur Datierung der Apostelgeschichte: Ein Ordnungsversuch im chronologischen Chaos - Backhaus, Knut (Zeitschrift für die neutestamentliche Wissenschaft, 2017)
The date of Acts is currently a center of robust controversy. The compromise date (ca. 80/90 CE), which held considerable traction within scholarship, has become increasingly doubtful. Views that scholars have long deemed untenable– a late dating in the second century as well as very early dates– have now been revived. This paper examines the different approaches (i.e., strict and modified “early dating”, standard approach, relative and rigid “late dating”) and areas of argumentation (i.e., external attestation, life of Paul, relation to the gospels, narrated worlds of the first and second centuries, references to the reigns of Nero or Domitian, relation to the Pauline epistles and to Josephus, theological context, narrative perspective). The conclusion is that the relative “late dating” (ca. 100–130 CE) is the most viable solution.